Law state’s instauration: elaboration of constitution after transition - Louchene, Dalel; Tarek, Kheireddine (Journal of Human Sciences, 2022)
The purpose of this research is to study the mechanisms guaranteeing stability after a democratic transition in order to establish the state of law. However, the establishment of a universal constitutional model is impossible, some solutions are proposed to create democratic institutions according to the political context of the state.